English Education Students’ Understanding of Inflectional Morphology in The Jakarta Post Articles - Badri, Badri; Heriyanti, Lilis; Putri, Miftah Komala; Hekmatiar, Yusuf; Hasanah, Rosyidah (Journal of English Language and Education, 2026)
This study aims to describe students’ understanding of inflectional morphology in articles in The Jakarta Post. Previous research generally focuses only on identifying the types and frequency of inflectional morphemes in narrative texts, thus limited studies examining students' understanding in the context of authentic news texts. This study used a qualitative descriptive approach involving 15 English Education students who had taken a Morphology course. Data were collected through written tests and semi-structured interviews, then analyzed using the Spradley model. The results showed that students understood regular inflectional forms such as plural (-s/-es) and present participle (-ing) well, but experienced difficulties with irregular forms such as irregular past tense, irregular plural, and comparative and superlative. Difficulties were influenced by a lack of mastery of grammatical concepts, minimal practice in authentic texts, and limited vocabulary. These findings demonstrate the importance of integrating morphology learning with contextual text analysis to improve students’ understanding.